Combating corruption for sustainable public services in Malaysia: Smart governance matrix and corruption risk assessment - Wan Abdullah W.M.T.; Ahmad N.N.; Ariff A.M. (Universiti Malaysia Terengganu, 2023)
In a developing country such as Malaysia, combating corruption is needed to ensure its sustainable social and economic development. While numerous initiatives are undertaken to increase integrity in Malaysia, corruption issues in public services are still alarming. Corruption involving public institutions disrupts service efficiency, hampers confidence in public institutions, and increases the cost of public transactions. This study examines the link between the quality of governance environment and the ability to assess corruption risk. The quality of governance environment is proxied by five governance initiatives (Smart Governance Matrix) while the ability to predict corruption is represented by corruption risk assessment that consists of five indicators. Thirty-nine responded questionnaires, gathered from Integrity Officers in public institutions in Malaysia, are used in the analysis. We find that enterprise governance model, data governance model and human governance model are positively associated with the corruption risk assessment. Good governance environment, which is represented by the Smart Governance Matrix, increases the ability to assess corruption risks. The findings provide insight into the need to improve the governance environment in public services in Malaysia as it can work towards controlling corruption activities through its ability to comprehensively assess corruption risk. Penerbit UMT.